Cancer environmental immunotherapy: starving tumor cell to death by targeting TGFB on immune cell - Huang, Xing (J Immunother Cancer, 2021)
The blockage of intersectional communication between tumor and its metabolic and immune microenvironment is now considered a promising solution in treating cancer. Tumors have been identified as a special type of “wounds” that do not heal. Recent studies demonstrate that the lack of the transforming growth factor beta (TGFB) signaling pathway in CD4(+) helper T cells induces the remodeling of the intratumoral vascular tissue, like healing “wounds” in damaged tissues caused by tumor overgrowth, which consequently prevents tumor cells from receiving the required nutrients in their microenvironment. TGFB blockade thereby promotes damaged tissue healing, causing tumor cell death as a result of starvation, ultimately obtaining an effective anticancer immunotherapy immune response. Here, we comment on the TGFB-mediated crosstalk between immune system and nutritional supply, highlighting cancer immunotherapeutic strategies targeting environmental immune-metabolism interplay. Cancer environmental immunotherapy targeting TGFB might therefore become one of the most promising treatment strategies for patients with cancer.